A three-component reaction of arynes, sodium sulfinates, and aldehydes toward 2-sulfonyl benzyl alcohol derivatives. Issue 32 (3rd August 2021) - Hu, Yifan; Huang, Yuanting; Zhao, Xi; Gao, Yang; Li, Xianwei; Chen, Qian
Abstract : A direct route to 2-sulfonyl benzyl alcohol derivatives is achieved via three-component reactions of arynes, sodium sulfinates and aldehydes. Abstract : A novel three-component reaction of arynes, sodium sulfinates, and aldehydes under mild reaction conditions is described. This transformation provides a direct synthetic approach to 2-sulfonyl benzyl alcohol derivatives, which could be rapidly converted to diverse arylsulfur compounds via the transformation of the corresponding hydroxyl groups. Various aryne precursors, sodium arenesulfinates, and aromatic aldehydes can be effectively converted to the desired products in 40–84% yields (29 examples).